Sustainability Education for Namibian Youth to Advance Efficient Cookstoves and Energy Development - Lindgren, Samantha (Consilience, 2021)
Efficient cooking has long been of interest for its presence in multiple Sustainable Development Goals (SDGs) including Good Health and Well-Being, Affordable and Clean Energy, Quality Education, Gender Equality, and Climate Action among others. Widespread uptake of an efficient cooking device, such as an “improved” biomass or LPG cookstove, has the potential to contribute to progress on many simultaneous fronts. However, unlike other sustainable development and public health initiatives, few cookstove programs include all household stakeholders, and rarely are youth, the future and current users of cookstoves, purposefully engaged in diffusion efforts. The results of a 2019 stratified survey of 200 households in two rural towns, one serving as a control group, in the Hardap region of Namibia indicate that youth-oriented Education for Sustainable Development (ESD) programming may be an effective means of inspiring changes in energy-related attitudes and behaviors in the home and across the community. Households with children who were past participants of an ESD program in the Namib Desert demonstrated an awareness of, and an openness to, solar energy as an alternative to biomass. This study highlights the importance of broadening the definition of stakeholder in the cookstove and energy development sector to include children, and points to youth-oriented ESD as a potential framework for shifting attitudes and behaviors, generationally at home and across the community.